2014
DOI: 10.1111/ctr.12356
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia infection during allogeneic hematopoietic stem cell transplantation: a single‐center experience

Abstract: To examine risk factors for Stenotrophomonas maltophilia (S. maltophilia) infection during allogeneic hematopoietic stem cell transplantation (allo-HSCT), we retrospectively analyzed 259 patients who underwent allo-HSCT. Not only S. maltophilia infection but also S. maltophilia colonization was associated with mortality during allo-HSCT. Among 52 episodes in 39 patients in whom S. maltophilia was detected, documented infection developed in 33 episodes (25 patients). The onset of S. maltophilia infection in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…The colonization rate of 6.9% (20 patients) is comparable to other studies: Shiratori et al reported from a colonization rate of 6.4% (14/220 patients)[ 31 ]. In our study, colonized patients revealed in our study a significant lower OS in univariate analysis as well as in multivariate analysis (HR 1.982, 95% CI 1.091–3.597; p = 0.025) due to a higher NRM compared to non-colonized patients (5-year cumulative incidence of NRM: 40.1% vs. 16.2%, p = 0.003).…”
Section: Discussionsupporting
confidence: 84%
“…The colonization rate of 6.9% (20 patients) is comparable to other studies: Shiratori et al reported from a colonization rate of 6.4% (14/220 patients)[ 31 ]. In our study, colonized patients revealed in our study a significant lower OS in univariate analysis as well as in multivariate analysis (HR 1.982, 95% CI 1.091–3.597; p = 0.025) due to a higher NRM compared to non-colonized patients (5-year cumulative incidence of NRM: 40.1% vs. 16.2%, p = 0.003).…”
Section: Discussionsupporting
confidence: 84%
“…Yeshurun et al reported that 19 of 570 patients undergoing HSCT had invasive S. maltophilia infection and six died of infection. Shiratori et al reported that 25 of 259 patients undergoing HSCT had S. maltophilia infection and four died of septic shock or pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Stenotrophomonas maltophilia causes serious infectious complications in HSCT patients . Pyomyositis is a purulent infection of skeletal muscle that arises from hematogenous spread, usually with abscess formation .…”
mentioning
confidence: 99%
“…In recipients of HSCT, the risk factors for hospital-acquired pneumonia due to S. maltophilia include: (1) immunocompromised health status, (2) indwelling CVCs, (3) mechanical ventilation, (4) exposure to and duration of broad-spectrum antibiotic therapy, (5) prolonged hospitalization, (6) admission to an intensive care unit (ICU), and (7) presence of underlying lung disease such as chronic obstructive airway disease (25, 26). Treatment of ventilator-associated pneumonia (VAP) caused by S. maltophilia includes: (1) high dose trimethoprim-sulfamethoxazole (TMP-SMZ), which is still considered the drug of choice based on its excellent in vitro activity, and (2) an alternative antimicrobial therapy in patients having drug resistance, allergy, or adverse effects related to TMP-SMZ that includes a new fluoroquinolone or a combination of doxycycline and aerosolized colistin (27, 28).…”
Section: Pneumonia Caused By S Maltophiliamentioning
confidence: 99%